2012
DOI: 10.1084/jem.20120914
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin 1 is expressed on thymus-derived natural regulatory T cells, but not mucosa-generated induced Foxp3+ T reg cells

Abstract: Neuropilin-1 surface expression discriminates between nT reg cells with stable expression and Nrp1 low iT reg cells showing inducible expression under inflammatory conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
513
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 542 publications
(552 citation statements)
references
References 69 publications
(104 reference statements)
33
513
2
4
Order By: Relevance
“…Up to now, no solid marker to discriminate thymus-derived and peripherally induced Tregs was found. Recently, Nrp-1 was proposed to be expressed at high levels on thymus-derived opposed to peripherally induced Tregs (40,41). In this study, we found lower H2BeGFP levels in Nrp1 high compared with Nrp1 low Tregs.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Up to now, no solid marker to discriminate thymus-derived and peripherally induced Tregs was found. Recently, Nrp-1 was proposed to be expressed at high levels on thymus-derived opposed to peripherally induced Tregs (40,41). In this study, we found lower H2BeGFP levels in Nrp1 high compared with Nrp1 low Tregs.…”
Section: Discussionsupporting
confidence: 57%
“…Next, we sought to investigate the proliferation history of Treg populations defined by Treg-specific markers. The transcription factor Helios (39) and the surface molecule Nrp1 (40,41) were recently proposed to discriminate thymic-derived and peripherally induced Tregs. As revealed by H2BeGFP levels of the respective Treg populations in secondary lymphoid organs, Helios + and Nrp1 high Tregs had proliferated more than Helios 2 or Nrp1 low Tregs (Fig.…”
Section: Proliferation History Of Peripheral Treg Subsetsmentioning
confidence: 99%
“…Although Nrp-1 was initially proposed as a naturally occurring T reg -cell-specific marker (14,17), additional studies have shown that peripherally induced T reg cells are capable of up-regulating Nrp-1, especially in the lung (18,19). Consequently, it remains uncertain whether the expanded T reg cells in the lungs of BeOexposed HLA-DP2 Tg mice are naturally occurring or peripherally induced.…”
Section: Discussionmentioning
confidence: 99%
“…We next addressed the physiological relevance of KLF2 by examining peripheral Treg (pTreg) populations under homeostatic conditions. Reports indicate that Helios (an Ikaros transcription factor family member) and Neuropilin 1 (Nrp1, a membrane-bound surface receptor) are preferentially but not exclusively expressed by tTregs relative to pTregs (20)(21)(22)(23)(24)(25). To determine whether either of these molecules were appropriate surrogates for pTreg identification, we initially characterized expression patterns within the entire regulatory Tcell compartment.…”
Section: Klf2 Is Required For the Ex Vivo Generation Of Itregsmentioning
confidence: 99%